2020
DOI: 10.1080/15592294.2020.1767374
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of diagnostic criteria for upper urinary tract urothelial carcinoma based on genome-wide DNA methylation analysis

Abstract: The aim of this study was to develop a less invasive and accurate diagnostic system for upper urinary tract urothelial carcinoma (UTUC) based on genome-wide DNA methylation profiling. Genome-wide DNA methylation screening was performed using the Infinium HumanMethylation450 BeadChip, and DNA methylation quantification was verified using pyrosequencing. We analysed 26 samples of normal control urothelial tissue (C), an initial cohort of 62 samples (31 samples of non-cancerous urothelium [N] from UTUC patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 43 publications
(55 reference statements)
2
15
0
Order By: Relevance
“…Moreover, among the genes included in Table 2 , only three showed a significant correlation between the levels of DNA methylation and expression ( P < 0.05 and r < −0.2 or r > 0.2) (Additional file 1 : Table S5). These findings are consistent with our previous studies, which revealed that even DNA methylation alterations at CpG sites not involved in regulating the expression of functionally important genes can become excellent surrogate markers for DNA methylation diagnostics [ 41 , 42 ]. Particularly at the carcinogenic risk stage, but not in established cancers, it is feasible that DNA methylation alterations would not yet have expanded immediately to involve important tumor-related genes [ 19 22 ].…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, among the genes included in Table 2 , only three showed a significant correlation between the levels of DNA methylation and expression ( P < 0.05 and r < −0.2 or r > 0.2) (Additional file 1 : Table S5). These findings are consistent with our previous studies, which revealed that even DNA methylation alterations at CpG sites not involved in regulating the expression of functionally important genes can become excellent surrogate markers for DNA methylation diagnostics [ 41 , 42 ]. Particularly at the carcinogenic risk stage, but not in established cancers, it is feasible that DNA methylation alterations would not yet have expanded immediately to involve important tumor-related genes [ 19 22 ].…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, other marker CpG sites, position 1 of cg02046247 and position 2 of cg19918599, included in Table 3 are located outside CpG islands (open sea regions) in intergenic regions and would not participate in regulating the expression of specific genes. This is consistent with the results of our previous studies, indicating that even DNA methylation alterations at CpG sites not involved in the expression of functionally important genes would be potentially excellent surrogate markers for cancer diagnostics (Fujimoto et al 2020 ; Nagashio et al 2011 ). In general, most 5-methylcytosine residues seem to be controlled in a coordinated manner with their neighbors, rather than being independent, resulting in a domain wherein all CpG sites show largely similar methylation levels (Yokoyama et al 2015 ).…”
Section: Discussionsupporting
confidence: 92%
“…The PCR and sequencing primers were designed using PSQ Assay Design Software Version 1.0.6 (Biotage, Uppsala, Sweden). To overcome any PCR bias, we optimized the PCR conditions: 0%, 50%, and 100% of the fully methylated control DNA (Epitect methylated human control DNA, QIAGEN) were used as a template to test the linearity of the protocol, as described previously (Fujimoto et al 2020 ; Nagashio et al 2011 ). The optimized PCR conditions, i.e., PCR cycle and DNA polymerase, for each primer set are summarized in Table S2.…”
Section: Methodsmentioning
confidence: 99%
“…The PCR and sequencing primers for the promoter regions of the TRIM58 and ZNF132 genes were designed using PSQ Assay Design Software Version 1.0.6 (Biotage, Uppsala, Sweden). To overcome any PCR bias, we optimized the PCR conditions: 0, 50 and 100% of the fully methylated control DNA (Epitect methylated human control DNA, QIAGEN) was used as a template, as described previously ( 24 ), and the linearity of the measured values and their consistency with the theoretical values were confirmed. As a result of this optimization experiment, both PCR reactions were performed using HotStarTaq DNA polymerase (QIAGEN).…”
Section: Methodsmentioning
confidence: 99%